Diagnosis by laparoscopy: a case report of peritoneal lymphomatosis secondary to Burkitt lymphoma in a patient with suspected ovarian cancer - Thompson, Annemarie; Schenken, Claire M.; Armstrong, Julia; Spencer, Nicole M.; Bojanini, Leyla; McCann, Georgia; Lyons, Yasmin A. (Annals of Lymphoma, 2026)
Background: Peritoneal lymphomatosis is a rare manifestation of non-Hodgkin’s lymphoma in which the lymphoma seeds the peritoneum. Peritoneal lymphomatosis can be seen with aggressive/high-grade B-cell lymphomas such as diffuse large B-cell lymphoma, or, more rarely, Burkitt lymphoma. More commonly, ovarian or gastrointestinal malignancies metastasize to the peritoneum as peritoneal carcinomatosis that closely mimics peritoneal lymphomatosis.Case Description: We report a case of a 45-year-old female who presented with abdominal distension and computed tomography (CT) findings suggestive of peritoneal carcinomatosis. She underwent inconclusive paracentesis, CT-guided omental biopsy, esophagogastroduodenoscopy and colonoscopy. She was ultimately diagnosed with peritoneal lymphomatosis secondary to Burkitt lymphoma by laparoscopic-directed omental biopsies. Burkitt lymphoma was confirmed by flow cytometry and fluorescence in situ hybridization (FISH) showing IGH::MYC t(8;14). Following diagnosis, she received one cycle of chemotherapy DA-EPOCH-R (rituximab, doxorubicin, etoposide, vincristine, cyclophosphamide, prednisone). She was subsequently diagnosed with central nervous system involvement and underwent intrathecal and systemic methotrexate followed by two cycles of R-IVAC (rituximab, ifosfamide, etoposide, cytarabine) and one cycle of R-CODOX-M (rituximab, cyclophosphamide, vincristine, doxorubicin, methotrexate). She had no evidence of disease on PET imaging 6 months after treatment.Conclusions: Because imaging findings of peritoneal carcinomatosis and peritoneal lymphomatosis often overlap, prompt tissue biopsy is essential to guide management, as peritoneal lymphomatosis is treated with chemotherapy alone, while peritoneal carcinomatosis often requires surgical debulking and misdiagnosis may result in unnecessary surgery.